The Impact of Property Tax Increase on the Banking Sector in Korea with a Focus on the Value of Collateral - Kim, Myungkyoo (2007)
Banks enhance the efficiency of economy by intermediating between the borrowers who do not have money but business plans and lenders who have money surplus. However, in the process of intermediation the banks are exposed to diverse risks such as credit risk, liquidity risk, and so on. Therefore it is the core of banking business management how to manage such risks.